Targeted Financial Sanctions of the United Nations and the European Union: Attribution of Criminal Character - Steponėnaitė, Viltė Kristina Kristina (Teisė, 2019)
[full article and abstract in Lithuanian; abstract in English] The article analyses the character of the targeted financial sanctions as imposed by the United Nations and the European Union. The article portrays that United Nations and European Union institutions, the Court of Justice of the European Union and part of the scholars do not recognize the criminal character of the measures currently, and arguargues that in the context of the international human rights law these measures shall be considered of the criminal character. Summary The article analyses whether targeted financial sanctions as imposed by the United Nations and the European Union shall be considered of criminal character. The article portrays that United Nations and European Union institutions, the Court of Justice of the European Union and part of the scholars do not recognize the criminal character of the measures. The article argues this position cannot be considered as well-grounded and that the measures, as being imposed for serious offences and causing very serious indefinite long-term effects on subject’s life and activities, on the scope of fundamental rights and freedoms, shall be considered of criminal character.